L’habitant chercheur : nouvelle figure des sciences impliquées - Olivier Bories; Claire Ribrault; Flore Causse-Kaposztas; Sylvie Houte; Eric Bouhet; Estelle Barbeau; Céline Faure (Projets de Paysage)
Our article presents a scientific collaboration between inhabitants and researchers, in which the researchers are asked to conduct research based on questions raised by the inhabitants. The research project looks at the relations of the inhabitants to nature, the environment and the landscape. The group of inhabitants and researchers focus on private gardens as spaces which preserve biodiversity and construct the landscape. This experiment confers a central role to the co-construction of methods and knowledge over time. It implies employing a special didactic two-way researcher-inhabitant approach. We introduce the figure of the “inhabitant-researcher” to express the changes in posture among the participants.